Unraveling the oxidation mechanism of an AlCoCrFeNi high-entropy alloy at 1100 °C. (December 2022) - Lu, Jie; Ren, Guoliang; Chen, Ying; Zhang, Han; Li, Ling; Huang, Aihui; Liu, Xuanzhen; Cai, Huangyue; Shan, Xiao; Luo, Lirong; Zhang, Xiancheng; Zhao, Xiaofeng
Abstract: This work aims to study the effect of elemental sluggish diffusion on the oxidation resistance of Al2 O3 -forming high-entropy alloys (HEAs). We compare the oxidation behavior of an AlCoCrFeNi HEA with that of two conventional Al2 O3 -forming alloys (FeCrAl and NiCoCrAl) and calculate the diffusivities of metal elements in the alloys using hybrid molecular dynamics (MD) and Monte Carlo (MC) simulations. It is clearly demonstrated in this study that the one order of magnitude lower diffusion rate of Al in the AlCoCrFeNi HEA is beneficial to lower the oxidation rate and inhibit the interface rumpling, thus improving the oxidation resistance. Graphical Abstract: ga1 Highlights: The hybrid molecular dynamics (MD) and Monte Carlo (MC) simulations are utilized to calculate the diffusivities of metal elements. The much lower diffusion rate of Al in the AlCoCrFeNi HEA slows down the oxidation rate. The growth of columnar grains in the Al2 O3 scale formed on the AlCoCrFeNi HEA is facilitated. The absence of interface rumpling is attributed to the lower growth stress and the potentially stronger creep resistance.